ANEMIA PADA KEHAMILAN DENGAN TINGKAT ASFIKSIA NEONATORUM PADA IBU BERSALIN - Dian Aprilia; Dewa Ayu Surinati; Suratiah * (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
This study aims to determine the relationship between anemia in pregnancy with neonatal asphyxia levels in mothers giving birth at Wangaya Hospital. This type of research is non-experimental with a correlational research design with aapproach retrospective using a purposive sampling technique. The number of samples is 108 people. The results of the study used thetest Spearman rank and obtained a value of p = 0,000 p value α (0.05). This means that there is an association of anemia in pregnancies with neonatal asphyxia levels in maternity in Wangaya Hospital in 2019, the r value of 0.705 shows a strong correlation between the variables of anemia in pregnancy with neonatal asphyxia in maternity. The correlation coefficient value is positive, indicating the more mild anemia in pregnancy, the lighter the level of neonatal asphyxia in maternity in Wangaya Hospital in 2019.